Pengaruh Kecerdasan Emosional dan Minat Belajar terhadap Penguasaan Konsep Matematika Siswa SMAN di Kecamatan Kebon Jeruk - Mira Gusniwati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2015)
The purpose of this study is to determine the influence of Emotional Question and interest in learning towards mastery of mathematical concepts. The hypothesis of this study include: (1) there is a direct effect of emotional question to mastery of mathematical concepts; (2) there is a direct effect of emotional question to interest in learning math; (3) there is a direct effect of interest in learning math to mastery of mathematical concepts; (4) there is an indirect effect of emotional question toward mastery of mathematical concepts through interest in learning mathematical. The method used in this study is a survey method with data analysis using path analysis. Affordable population are students of class x1 school year 2013/2014 public senior high school in Kebon Jeruk, west Jakarta. Sample size is 70 student with the sampling technique used is random sampling taken from 2 public school. Research instrument used is questioner and test of mastery of mathematical concepts. Retrieved hypothesis testing results the following conclutions. Hypothesis testing results show that: (1) there is a direct effect of emotional question to mastery of mathematical concepts; (2) there is a direct effect of emotional question to interest in learning math; (3) there is a direct effect of interest in learning math to mastery of mathematical concepts; (4) there is an indirect effect of emotional question toward mastery of mathematical concepts through interest in learning mathematical. Keywords: emotional question, interest in learning, mathematical concepts.